2021
DOI: 10.1002/ijc.33842
|View full text |Cite
|
Sign up to set email alerts
|

Tumor DNA‐methylome derived epigenetic fingerprint identifies HPV‐negative head and neck patients at risk for locoregional recurrence after postoperative radiochemotherapy

Abstract: Biomarkers with relevance for loco-regional therapy are needed in human papillomavirus negative aka HPV(À) head and neck squamous cell carcinoma (HNSCC). Based on the premise that DNA methylation pattern is highly conserved, we sought to develop a reliable and robust methylome-based classifier identifying HPV(À) HNSCC patients at risk for loco-regional recurrence (LR) and all-event progression after postoperative radiochemotherapy (PORT-C). The training cohort consisted of HPV-DNA negative HNSCC patients (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Multivariate analysis of the same study by Tawk et al [17] also showed that HICR high-risk tumors were enriched for younger patients with hypoxic tumors (15-gene hypoxia signature) and elevated 5-miRNA scores. The 5-miRNA signature (hsa-let-7g-3p, hsa-miR-6508-5p, hsa-miR-210-5p, hsa-miR-4306, and hsa-miR-7161-3p) was previously shown as a strong and independent prognostic factor for disease recurrence and survival of patients with HPV-negative HNSCC [23].…”
Section: Dna Methylation Profiles In Hpv-negative Hnsccmentioning
confidence: 75%
See 2 more Smart Citations
“…Multivariate analysis of the same study by Tawk et al [17] also showed that HICR high-risk tumors were enriched for younger patients with hypoxic tumors (15-gene hypoxia signature) and elevated 5-miRNA scores. The 5-miRNA signature (hsa-let-7g-3p, hsa-miR-6508-5p, hsa-miR-210-5p, hsa-miR-4306, and hsa-miR-7161-3p) was previously shown as a strong and independent prognostic factor for disease recurrence and survival of patients with HPV-negative HNSCC [23].…”
Section: Dna Methylation Profiles In Hpv-negative Hnsccmentioning
confidence: 75%
“…Regarding the role of DNA methylation profiles in HPV-negative HNSCC, hypermethylation of MGMT and COL1A2 is another example that can be considered a clinically valuable prognostic factor since there is a lack of biomarkers for HPV-negative HNSCC in general. Additionally, the future application of 38 differentially methylated probes as biomarkers to classify disease recurrence, distant metastasis, and overall survival [17] is also clinically valuable, as it may help stratify HPV-negative HNSCC patients. This could provide more personalized treatment based on methylation profiles with hopefully better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with HPV DNA positivity were excluded, leaving 88 samples for validation. DNA methylation profiling was performed using Illumina 450 K microarrays (Illumina) as previously described ( 8 ). Functional normalization of DNA methylation was conducted using the minfi package in R ( 26, 27 ) and used as a validation cohort.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the presence of hypoxia in human papillomavirus (HPV)–negative patients with HNSCC confers poor prognosis. Patients with hypoxic tumors may benefit from stratified therapy intensification ( 8, 9 ). However, the robust, feasible, and reliable detection of tumor hypoxia remains a major challenge.…”
Section: Introductionmentioning
confidence: 99%